Object oriented programming : data preparation and visualization of FEM models - Azevedo, Álvaro F. M. (1997)
In this paper two object oriented applications are described. The former is intended to generate data associated with the finite element method (FEM) and the later is a three-dimensional visualization tool named 3DMesh. Both are based on the principles of object oriented programming, namely encapsulation, inheritance and polymorphism. To support the preparation of FEM data, a language named 3DO was developed. Its syntax is similar to a subset of the C++ programming language. 3DO is based on object construction and modification by methods that require a small number of arguments. With this tool, mesh generation, definition of properties and loads and mesh refinement can be performed with limited user effort, even when the model is complex. All the generated information can be visualized with the program 3DMesh. This application is based on the OpenGL library and uses the Microsoft Foundation Classes to simplify its integration in the MS-Windows environment. 3DMesh implements an interactive navigation technique that allows the visualization of the model interior, preserving its integrity. Model attributes and the results of the FEM analysis can also be visualized.